Reducing Anxiety and Improving Adherence in Kidney Transplant Recipients: A Cognitive Behavioral Intervention -Based Approach - Chao Zhong (22679885) (2025)
AbstractBackgroundPsychological resilience and medication adherence are pivotal for long-term outcomes following kidney transplantation. However, structured cognitive behavioral interventions (CBIs) remain underutilized in this patient population, despite their potential to address critical behavioral and emotional challenges.ObjectivesThis Study aimed to evaluate the efficacy of a structured CBI program in enhancing medication adherence, reducing anxiety symptoms, and improving self-awareness among kidney transplant recipients.Materials and MethodsIn a randomized controlled trial, 426 allogeneic kidney transplant recipients (2018–2024) were assigned to standard care (n=213) or CBI (n=213). The 12-week CBI included digital psychoeducation, individualized psychotherapy, and peer support. Primary outcomes were adherence rate, Self-Rating Anxiety Scale (SAS) score, and self-awareness level. Data were analyzed using t-tests, chi-square tests, and logistic regression models.ResultsCBI significantly improved adherence (92.5% vs. 66.0%, +26.5%, p<0.001) and reduced anxiety scores by 38.9% (36.8±8.6 vs. 60.2±14.3, p<0.001). Improvements in self-awareness were 3.2-fold higher (p<0.05), with notable gains in physical and emotional quality-of-life domains (p<0.001 for both). Subgroup analyses showed consistent benefits across age and socioeconomic groups.ConclusionsA structured CBI significantly improves psychological resilience, alleviates anxiety, and enhances behavioral adherence in kidney transplant recipients, showing strong potential for broader implementation as an effective adjunct to standard care.